(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An Efficient tunable subthreshold logic circuit planned by utilizing adaptive feedback equalization circuit. This circuit utilized in the Ladner Fischer adder. This circuit utilized in a successive advanced logic circuit to moderate the cycle variety impacts and lessen the prevailing spillage energy part in the subthreshold area. Feedback equalizer circuit changes the switching edge of its inverter. It depends on the output of the flip-flop in the past cycle to lessen the charging and releasing season of the flip-flop’s information capacitance. Besides, the more modest info capacitance of the feedback equalizer lessens the switching season of the last door in the combinational logic block. Likewise present point by point energy-performance models of the adaptive feedback equalizer circuit.